Anatomy of trisomy 12. Issue 5 (3rd May 2016) - Roberts, Wallisa; Zurada, Anna; Zurada‐ZieliŃSka, Agnieszka; Gielecki, Jerzy; Loukas, Marios
Abstract : Trisomy 12 is a rare aneuploidy and fetuses with this defect tend to spontaneously abort. However, mosaicism allows this anomaly to manifest itself in live births. Due to the fact that mosaicism represents a common genetic abnormality, trisomy 12 is encountered more frequently than expected at a rate of 1 in 500 live births. Thus, it is imperative that medical practitioners are aware of this aneuploidy. Moreover, this genetic disorder may result from a complete or partial duplication of chromosome 12. A partial duplication may refer to a specific segment on the chromosome, or one of the arms. On the other hand, a complete duplication refers to duplication of both arms of chromosome 12. The combination of mosaicism and the variable duplication sites has led to variable phenotypes ranging from normal phenotype to Potter sequence to gross physical defects of the various organ systems. This article provides a review of the common anatomical variation of the different types of trisomy 12. This review revealed that further documentation is needed for trisomy 12q and complete trisomy 12 to clearly delineate the constellation of anomalies that characterize each genetic defect. Clin. Anat. 29:633–637, 2016. © 2016 Wiley Periodicals, Inc.